Improvement of Indonesian Learning Results In Vocabulary Materials With The Make A Match Learning Model In Class 2nd Students of Sd Negeri 3 Getas Academic Year 2020/2021 - Hesty Anjar Hanifah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This study aims to improve understanding of vocabulary and their meanings by applying modeling techniques to grade II students in elementary schools. This study was designed in two cycles, with the research subjects of grade II students of SD N 3 Getas in Kaloran District, Temangggung Regency with a total number of students. 19 students. The research design used was the Classroom Action Research (PTK) spiral model from Kemmis and Taggart which included four stages of research, namely planning, implementing, observing, and reflecting. Students' understanding of the meaning of vocabulary has increased each cycle. Increased understanding of the meaning of students' vocabulary can be seen from the average of the first cycle only 36.8%. While in cycle II the average score increased by 84.21. It was concluded that using the Make a Match type learning model which was carried out in accordance with the learning steps included preparing question and answer cards, dividing students and cards into two parts, mixing the cards. randomly, dividing cards and explaining the learning process, presenting the results of matching cards, making learning conclusions, providing evaluation and closing the learning process in Indonesian subjects can improve learning outcomes for grade 2 students at SD N 3 Getas, Kaloran District, Temanggung Regency